Labour productivity growth (Edition 2013) (OECD Productivity Statistics, 2013)
This dataset includes statistical indicators on labour productivity defined as gross domestic product (GDP) per hour worked. GDP for each country is expressed in national currency at constant prices whereas GDP for country groups/zones is expressed in USD at constant prices and PPPs. Labour productivity growth can also be analyzed by hours worked, labour productivity growth rate, GDP annual compound rate and more. Data are presented as annual datapoints from 1970 onwards